Los think tanks en el gabinete: Una exploración del caso chileno (2006-2014) - Olivares L., Alejandro; González-Bustamante, Bastián; Meneses, Javiera; Rodríguez, Matías (Revista de Sociología, 2015)
This paper analyses the main factors that allow access to Michelle Bachelet’s cabinet (2006-2010) and to Sebastián Piñera’s cabinet (2010-2014) in Chile, with focus on the influence of participation in think tanks to access the cabinet. We work with a database of 102 cases corresponding to 90 people who were appointed ministers in the mentioned period. We present a description of the group, and a Qualitative Comparative Analysis (QCA). The results find that think tank membership is a relevant factor for appointments in political and economic ministries during both governments.